Excited-State-Altering Ratiometric Fluorescent Probes for the Response of β-Galactosidase in Senescent Cells - Ya-Nan Han; Lei Dong; Lu-Lu Sun; Wen-Jia Li; Jianjing Xie; Congyu Li; Shuhui Ren; Zhan Zhang; Hai-Hao Han; Zhong Zhang (Molecules)
β-galactosidase (β-Gal) has emerged as a pivotal biomarker for the comprehensive investigation of diseases associated with cellular senescence. The development of a fluorescent sensor is of considerable importance for precisely detecting the activity and spatial distribution of β-Gal. In this study, we developed two excited-state-altering responsive fluorescent sensors (TF1 and TF2) for ratiometric detection of β-Gal. Two TCF dyes, composed of tricyanofuran (TCF) and naphthol units, feature electron “pull–push” systems and are quenched fluorescence by β-Gal. Upon β-Gal hydrolysis, a significant ratiometric shift in absorption from ca. 475 nm to 630 nm is observed, accompanied by the emergence of a fluorescence signal at ca. 660 nm. The enzyme-responsive optical red-shifts are attributed to the excited-state transition from intramolecular charge transfer (ICT) state to local excited (LE) state, which was confirmed by density functional theory (DFT) calculations. Both fluorescent sensors display exceptional sensitivity and selectivity for the response of β-Gal in PBS solution and are capable of tracking β-Gal within senescent A549 cells. This study introduces a framework for developing multimodal optical probes by systematically modulating excited-state properties, demonstrating their utility in senescence studies, diagnostic assay design, and therapeutic assessment.